Primary Disseminated Intra-abdominal Hydatid Disease: A Case Report (BIRDEM Medical Journal, 2017)
Hydatid disease in human is common and liver is the most common site of involvement followed by lungs. Within the abdomen, hydatid disease can disseminate to involve spleen, pancreas, mesentery, kidney, ovary, gut, supra-renal glands etc. Such disseminations are usually secondary to rupture of a cyst: spontaneous, iatrogenic or traumatic. Without such a history, primary disseminated intra-abdominal hydatidosis is rare. Here we present such a case.Birdem Med J 2018; 8(1): 75-76